Subjective Cognitive Decline May Be Associated With Post-operative Delirium in Patients Undergoing Total Hip Replacement: The PNDABLE Study - Lin, Xu; Liu, Fanghao; Wang, Bin; Dong, Rui; Sun, Lixin; Wang, Mingshan; Bi, Yanlin (Frontiers in Aging Neuroscience, 2021)
Objective: Subjective cognitive decline (SCD) is associated with an increased risk of clinical cognitive disorders. Post-operative delirium (POD) is a common complication after total hip replacement. We aimed to investigate the relationship between SCD and POD in patients undergoing total hip replacement. Methods: Our study recruited 214 cognitively intact individuals from the Perioperative Neurocognitive Disorder And Biomarker Lifestyle (PNDABLE) study in the final analysis. SCD was diagnosed with Subjective Cognitive Decline Scale (SCDS), Mini-Mental State Examination (MMSE), and Montreal Cognitive Assessment (MoCA). The incidence of POD was evaluated by using Confusion Assessment Method (CAM), and POD severity was measured by using the Memorial Delirium Assessment Scale (MDAS). Preoperative cerebrospinal fluid (CSF) Aβ40, Aβ42, T-tau, and P-tau levels were measured by enzyme-linked immune-sorbent assay (ELISA). Results: Overall, the incidence of POD was 26.64% (57/214), including 32.43% (36/111) in the SCD group and 20.39% (21/103) in the NC group. With the increase of age, the incidence of POD in all age groups increased (P < 0.05). Logistic regression analysis showed that after adjusting for SCD, Aβ42, Aβ40, P-tau, and T-tau, SCD (OR 2.32, CI 1.18–4.55, P = 0.01) and the increased CSF level of P-tau (OR 1.04, CI 1.01–1.06, P < 0.001) were risk factors for POD, while the level of aβ42 (OR 0.99, CI 0.99–1.00, P < 0.001) was a protective factor for POD. Conclusion: SCD is one of the preoperative risk factors for POD. Clinical Trial Registration: This study was registered at China Clinical Trial Registry (Chictr200033439).